(x^2 - y^2) / (x - y)
Apply the difference of squares formula:
(x + y)(x - y) / (x - y)
Assuming x is not equal to y, we can cancel terms leaving
x + y
When x = y, the denominator becomes 0, and the equation gives no information.
-3
By factoring I get x-3 divided by x+3
x-8
xsquared minus x minus 72
(x + 2)(x - 9)
-3
x + 1
By factoring I get x-3 divided by x+3
x-8
x - 3
x - 5
24
7x + 8
x = ? 42 = x squared minus x
x^2-4x/x^2-6x+8 = x(x-4)/(x-2)(x-4) = x/(x-2)
x >2 x2 - x - 6/(x2 - 4) (x + 2)(x - 3)/(x + 2)(x - 2) cross out x + 2 (x - 3)/(x - 2) this is the most simplified this can be
First, factorising, we get: x2 - 6x - 16 = (x - 8)(x + 2). Then, (x2 - 6x - 16) / (x - 8) = x + 2.